Female college students’ knowledge, attitudes and practices about breast-self examination and behavioral-related risk factors for breast cancer: A cross-sectional analysis. (2015)
Background: Breast cancer is a growing public health problem worldwide. Breast-self examination (BSE) is an inexpensive strategy proposed to improve early detection behaviors. Behavioral risk factors are crucial for cancer control. More than half of breast cancer cases can be prevented through behavior change. This study aimed to describe and establish assocations between the knowledge, attitudes and practices of breast-self examination, the knowledge about breast cancer risk and behavioral-related risk factors for breast cancer among female college students in Bogotá, Colombia. Methods: A cross-sectional study was carried out involving data from 628 young female students. Data for BSE were collected using a validated tool and the Behavioral Risk Factors Surveillance System (BRFSS) was used for lifestyle-related variables. Results: Women were a mean age of 21.7±11.8 years old. Fifty-seven percent of the women knew how to carry out BSE, although only 26.3% perfom it monthly. Further, a sedentary lifestyle was found in 53.3% of women and similar prevalences were observed for other behavioral variables. BSE was associated with age (p = 0.02), socioeconomic status (p < 0.001), knowledge about risk factors (p < 0.001) and unhealthy lifestyles (p < 0.001). Conclusions: There exists a low level of knowledge and practice of BSE among female college students. This population is at a high-risk of breast cancer beacuse of the critical prevalences of some behaviors related to unhealthy lifestyles found in this study. Further health-promotion strategies are warranted.